2. 52 + 3 : 710 - 54 : 33
2.52 + 3: 710 – 54: 33
113.72 - 72.12-49
2.52 + 3:710-54:33
113.7² - 7².12 - 49
= 113.49 - 49.12 - 49
= 49.(113 - 12 - 1)
= 49.100
= 4900
------------
2.5² + 3 : 71⁰ - 54 : 3³
2.25 + 3 : 1 - 54 : 27
= 50 + 3 - 2
= 51
113.7² - 7².12 - 49
= 113.49 - 49.12 - 49
= 49.(113 - 12 - 1)
= 49.100
= 4900
2.5² + 3 : 71⁰ - 54 : 3³
2.25 + 3 : 1 - 54 : 27
= 50 + 3 - 2
= 51
2.52+33:710-54:33
113.72-72.12-49
2.5² + 33 : 71⁰ - 54 : 3³
= 2.25 + 33 : 1 - 54 : 27
= 50 + 33 - 2
= 81
--------
113.7² - 7².12 - 49
= 113.49 - 49.12 - 49
= 49.(113 - 12 - 1)
= 49.100
= 4900
Thực hiện phép tính:
a) 75 - ( 3 . 5 2 - 4 . 2 3 )
b) 2 . 5 2 + 3 : 71 0 - 54 : 3 3
c) 150 + 50 : 5 - 2 . 3 2
d) 5 . 3 2 - 32 : 4 2
ddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddddđ6666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666666
Thực hiện phép tính:
a, 75 - 3 . 5 2 - 4 . 2 3
b, 2 . 5 2 + 3 : 71 0 - 54 : 3 3
c, 150 + 50 : 5 - 2 . 3 2
d, 5 . 3 2 - 32 : 4 2
a, 75 - 3 . 5 2 - 4 . 2 3
= 75 – (3.25 – 4.8)
= 75 – 43 = 32
b, 2 . 5 2 + 3 : 71 0 - 54 : 3 3
= 50 + 3 – 2 = 51
c, 150 + 50 : 5 - 2 . 3 2
= 150 + 10 – 18 = 142
d, 5 . 3 2 - 32 : 4 2
= 5.9 – 32:16 = 45 – 2 = 43
1)Tìm số dư của phép chia B cho 4
B=1+3+32+33+...+3100
2)Thu gọn C=5-52+53-54+...+52023-52024
Bài 1:
$B=1+3+3^2+3^3+...+3^{100}$
$=1+(3+3^2)+(3^3+3^4)+...+(3^{99}+3^{100})$
$=1+3(1+3)+3^3(1+3)+...+3^{99}(1+3)$
$=1+(1+3)(3+3^3+...+3^{99})=1+4(3+3^3+....+3^{99})$
$\Rightarrow B$ chia 4 dư 1.
Bài 2:
$C=5-5^2+5^3-5^4+...+5^{2023}-5^{2024}$
$5C=5^2-5^3+5^4-5^5+...+5^{2024}-5^{2025}$
$\Rightarrow C+5C=5-5^{2025}$
$6C=5-5^{2025}$
$C=\frac{5-5^{2025}}{6}$
50. √(98-16√3)
51. √(2-√3)
52. √(4+√15)
53. √(5-√21)
54. √(6-√35)
55. √(2+√3)
56. √(4-√15)
57. √(8-√55)
58. √(7+√33)
59. √(6+√35)
60. √(7-3√5)
50) \(\sqrt{98-16\sqrt{3}}=4\sqrt{6}-\sqrt{2}\)
51) \(\sqrt{2-\sqrt{3}}=\dfrac{\sqrt{4-2\sqrt{3}}}{\sqrt{2}}=\dfrac{\sqrt{3}-1}{\sqrt{2}}=\dfrac{\sqrt{6}-\sqrt{2}}{2}\)
52) \(\sqrt{4+\sqrt{15}}=\dfrac{\sqrt{8+2\sqrt{15}}}{\sqrt{2}}=\dfrac{\sqrt{5}+\sqrt{3}}{\sqrt{2}}=\dfrac{\sqrt{10}+\sqrt{6}}{2}\)
53) \(\sqrt{5-\sqrt{21}}=\dfrac{\sqrt{10-2\sqrt{21}}}{\sqrt{2}}=\dfrac{\sqrt{14}-\sqrt{6}}{2}\)
54) \(\sqrt{6-\sqrt{35}}=\dfrac{\sqrt{12-2\sqrt{35}}}{\sqrt{2}}=\dfrac{\sqrt{14}-\sqrt{10}}{2}\)
55) \(\sqrt{2+\sqrt{3}}=\dfrac{\sqrt{4+2\sqrt{3}}}{\sqrt{2}}=\dfrac{\sqrt{6}+\sqrt{2}}{2}\)
56) \(\sqrt{4-\sqrt{15}}=\dfrac{\sqrt{8-2\sqrt{15}}}{\sqrt{2}}=\dfrac{\sqrt{10}-\sqrt{6}}{2}\)
a) 25 - 53 : 52 + 12 : 22
b) 5 [ ( 85 - 35 : 7 ) : 8 + 90 ] - 50
c) 2. [ ( 7 - 33 : 32 ) 22 + 99 ] - 100
d) 27 : 22 + 54 : 53 . 24 - 3 . 25
e) ( 35 . 37 ) : 310 + 5 . 24 - 73 : 7
f) 32 . [ ( 52 - 3 ) : 11 ] - 24 + 2 . 103
g) ( 62007 - 62006 ) : 62006
h) ( 52001 - 52000 ) : 52000
i) ( 72005 + 72004 ) : 72004
j) ( 57 + 75 ) . ( 68 + 86 ) . ( 24 - 42 )
k) ( 57 + 79 ) . ( 54 + 56 ) . ( 33 . 3 - 92 )
l) [ ( 52 . 23) - 72 . 2 ) : 2 ] 6 - 7 . 25
Bài 1: Viết dấu , = vào chỗ chấm.
1 …. 2
3 … 1
3 ... 4
3 … 3
5 … 2
5 ... 2
5 … 4
2 … 3
1 ... 5
2 … 5
4 … 1
4 ... 4
4 … 3
5 … 5
2 ... 3
3 .... 5
1 .... 4
3 .... 1
1 < 2
3 > 1
3 < 4
3 = 3
5 > 2
5 > 4
2 < 3
1 < 5
4 > 1
4 = 4
4 > 3
5 = 5
2 < 3
3 < 5
1 < 4
3 > 1